Analysis of the Human Plasma Proteome Using Multi‐Nanoparticle Protein Corona for Detection of Alzheimer's Disease. Issue 2 (9th November 2020) - Corbo, Claudia; Li, Andrew A.; Poustchi, Hossein; Lee, Gha Young; Stacks, Sabrina; Molinaro, Roberto; Ma, Philip; Platt, Theo; Behzadi, Shahed; Langer, Robert; Farias, Vivek; Farokhzad, Omid C.
Abstract: As the population affected by Alzheimer's disease (AD) grows, so does the need for a noninvasive and accurate diagnostic tool. Current research reveals that AD pathogenesis begins as early as decades before clinical symptoms. The unique properties of nanoparticles (NPs) may be exploited to develop noninvasive diagnostics for early detection of AD. After exposure of NPs to biological fluids, the NP surface is altered by an unbiased but selective and reproducible adsorption of biomolecules commonly referred to as the biomolecular corona or protein corona (PC). The discovery that the plasma proteome may be differentially altered during health and disease leads to the concept of disease‐specific PCs. Herein, the disease‐specific PCs formed around NPs in a multi‐NPs platform are employed to successfully identify subtle changes in plasma protein patterns and detect AD (>92% specificity and ≈100% sensitivity). Similar discrimination power is achieved using banked plasma samples from a cohort of patients several years prior to their diagnosis with AD. With the nanoplatform's analytic ability to analyze pathological proteomic changes into a disease‐specific identifier, this promising, noninvasive technology with implications for early detection and intervention could benefit not only patients with AD but other diseases as well. Abstract : Protein coronas are formed on six varying nanoparticles in plasma of 11 Alzheimer's disease (AD), 16 healthy but later AD‐diagnosed, and 13 healthy patients. Random forest model detects prevalent AD with 99.96% sensitivity and 93.7% specificity, and incident AD with 97.6% sensitivity and 95.5% specificity. AD "importance scores" are also generated for more than 400 proteins from the protein corona.